Focusing the Relationship of Net Profit with the Determinant Attributes of Rural Entrepreneurs (Indian Journal of Extension Education, 2021)
With new strategies for agricultural growth and development, there is a need to explore the areas of rural entrepreneurship development on agriculture and allied sectors. The profit-making ability can be delineated with the help of the net profit of the enterprise. Keeping the background in mind, an attempt was made to study the net profit from the rural enterprises and its relationship with the predictor factors associated with the rural entrepreneurs. The study was purposively conducted in Darjeeling districts of West Bengal due to the availability of varied rural entrepreneurs. The purposive, multistage and random sampling procedures were followed to select 220 respondents. The data were collected with the help of semi-structured interview schedule through personal interview method. The results show that the rural entrepreneurs were having with low annual net profit of around 0.8 lakh. The correlation analysis delineated that age, annual income, land holding, family occupation, material possession, house type, management orientation, risk orientation, social participation, cosmopoliteness, training exposure and mass media exposure were positively and significantly associated with the net profit from the enterprise. The regression analysis indicated that age, annual income, land holding, adoption leadership, cosmopoliteness and training exposure were positively and significantly contributing towards characterizing the net profit from the enterprise. Family educational status, house type and risk orientation were also contributing significantly and negatively in case of characterizing net profit from the selected enterprises.